1999
DOI: 10.1007/s002800050959
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated p53 gene therapy has greater efficacy when combined with chemotherapy against human head and neck, ovarian, prostate, and breast cancer

Abstract: These results support the combination of p53 gene therapy with chemotherapy in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…Recent reports demonstrated that p53 missense mutants markedly reduced DNA binding of wild-type p53 Previous reports have demonstrated that the combination of adenoviral p53 and cisplatin was cooperative in ovarian, breast, lung, pancreatic, prostate, head and neck cancer cells expressing mutant p53. [10][11][12][26][27][28] Furthermore adenoviral p53 might enhance the effect of taxanes in lung and ovarian cancer. 9,10,12,29 Although it appears that p53 is not involved in paclitaxel-dependent apoptosis, 30 it may enhance adenoviral transduction efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports demonstrated that p53 missense mutants markedly reduced DNA binding of wild-type p53 Previous reports have demonstrated that the combination of adenoviral p53 and cisplatin was cooperative in ovarian, breast, lung, pancreatic, prostate, head and neck cancer cells expressing mutant p53. [10][11][12][26][27][28] Furthermore adenoviral p53 might enhance the effect of taxanes in lung and ovarian cancer. 9,10,12,29 Although it appears that p53 is not involved in paclitaxel-dependent apoptosis, 30 it may enhance adenoviral transduction efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][26][27][28] Furthermore adenoviral p53 might enhance the effect of taxanes in lung and ovarian cancer. 9,10,12,29 Although it appears that p53 is not involved in paclitaxel-dependent apoptosis, 30 it may enhance adenoviral transduction efficiency. 9 In our study, testing a representative number of 14 ovarian cancer cell lines, we observed that adenoviral p53 gene therapy improved paclitaxel and/or carboplatin chemotherapy in cell lines with mutant p53 as well as with wt p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, strategies combining adenovirus-mediated wild-type p53 gene transfer with DNA-damaging treatments, such as irradiation and chemotherapeutic agents, have also been explored in glioblastoma, lung, colorectal, ovarian, and head and neck cancers. These combination therapies involving p53 over expression have consistently demonstrated enhanced tumor suppressing activity, relative to single agents [11,12]. Finally, in androgen-independent prostate cancer cells, significant cytotoxicity has been previously reported with over expression of recombinant wild-type p53 using an adenovirus vector (Ad5CMV-P53) [13,14].…”
Section: Introductionmentioning
confidence: 95%
“…Preclinical data support this theory. 7,10,12 In addition, several reports have suggested that even drugs, which induce apoptosis independent of p53, can synergize with SCH58500 through multiple mechanisms. 12,17 Results from early clinical trials using SCH58500 by itself support optimism for the future of this therapeutic approach to cancer treatment.…”
mentioning
confidence: 99%